Watchout : Paedophile Awareness Using 2d Animated Explainer Video - Mohamed Khedzer, Nur Shamina Shasha; Mohd Supian, Jessifa Joanna (Journal of Computing Technologies and Creative Content, 2019)
The recent case of paedophile, Richard Huckle has shocked the Malaysian nation on how fragile and dangerous when the Internet is being used to save abusive pictures and videos of children. Most children are pampered by gadgets. This can cause them to be exposed to paedophile. The use of social media with parents uploading photos of their children to the general public is also a concern since awareness of these online predators is also low. This project aims is to help children to be cautious and know how to protect their own self from paedophile. The project is focus on delivering awareness of paedophile using 2D animated explainer video to make it more interesting and easier to understand by children. Research findings indicate that the explainer video helps in helping these children to understand ways to keep themselves safe. It is hope that this project will help and benefit both children and parents from the danger of paedophile.